Traditional importance of Indian butter tree and genetic resources management - Malik, S K; Choudhary, Ravish; Panwar, N S; Dhariwal, O P; Deswal, R P S; Pathak, Niti; Chaudhary, Rekha (Indian Horticulture, 2021)
Madhuca longifolia (Koenig) Macbr. (syn. M. indica Hamilton ex Gmet.) locally known as Mahua is an important tropical tree species having vital socio-economic value for the tribal populations of India. Vast genetic diversity of this species exists in tropical and sub-tropical parts of India. During various surveys, a total of 154 accessions were collected from different phyto-geographical regions. Substantial variability was present in collections made from west-central region especially from the states of Rajasthan, Gujarat, Madhya Pradesh and Uttar Pradesh and from southern states of Andhra Pradesh and Tamil Nadu. It is a multipurpose tree providing food, fuel, timber, green manure, oil, liquor and raw materials for several commercial products. In spite of its high economic value there are no improved cultivars or varieties developed in Mahua, however, some selections based on physico-chemical characters, period of fruit maturity and high seed oil content have been identified. Due to direct harvesting of economically important parts of this tree from natural habitat and deforestation, genetic diversity of Mahua is facing threat of extinction and requires immediate conservation efforts. Limited success achieved in cryopreservation of embryonic axes of this highly recalcitrant tropical tree species necessitates further refinement of protocol and also implementation of complimentary conservation strategy by maintaining field gene bank collections of promising genotypes. Urgent attention is also required for popularization and needful value addition to the commercial products of Mahua to attract present day market demand.